Cost analysis of Chronic Obstructive Pulmonary Disease (COPD): A systematic review - Celia Gutiérrez Villegas; María Paz-Zulueta; Manuel Herrero-Montes; Paula Parás-Bravo; María Madrazo Pérez (Health Economics Review, 2021)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a treatable disease with a high prevalence, and high morbidity associated with significant socioeconomic costs. Objective: To carry out a systematic review of the literature to analyze the main cost studies associated with COPD, in order to determine the main factors that influence the costs of the disease. Methods: Searches were conducted in PubMed, SCOPUS and Web of Science databases for cost studies on COPD published in English, between the years 2015 and 2020. The search terms were "COPD" OR "pulmonary disease, chronic obstructive", "cost*" OR "cost of illness", "economic impact" AND "burden of disease". The inclusion criteria included the identification of reported cost of the disease, economic burden, medical care expenses or use resources for COPD, the methodology used, data sources, and variables studied. Results: 18 publications were analyzed: 17 included direct health costs, 6 included direct non-medical costs, 12 analyzed indirect costs and two reported intangible costs. Most of the studies reported data for developed and European countries, with direct costs being the most studied. Trends were observed in multiple studies of direct and healthcare costs for European countries measured by patient and year, where the higher costs were associated with more severe COPD and a frequent history of exacerbations. The highest costs reported corresponded to hospitalizations and the associated pharmacological treatment. The importance of the loss of productivity and premature retirement within the profile of the COPD patient was also highlighted as the main generator of indirect costs of the disease. Conclusion: COPD generates substantial costs for the health system, mainly related to moderate to severe stages and the exacerbations and complications entailed. It is important to strengthen health systems with monitoring, evaluation and health education models that allow these patients to remain stable to avoid decompensation and subsequent hospitalizations.
Keywords: 330; Systematic review; Pulmonary disease; Chronic obstructive; Cost of illness; Health care costs; Investments